Prognostic value of the pretreatment Naples prognostic score in patients with colorectal cancer: a systematic review and meta-analysis - Hui Liu; Dailiang Zhu; Dequan Jiang; Huayang Pang; Xiaolian Yang (Frontiers in Oncology)
BackgroundThe prognostic significance of the Naples prognostic score (NPS) in colorectal cancer remains uncertain. This study aims to investigate the correlation between the pretreatment NPS and long-term oncological outcomes in patients with colorectal cancer.MethodsA comprehensive literature search of electronic databases, including PubMed, Embase, and Web of Science, was conducted up to July 1st, 2024. The primary outcomes assessed were survival outcomes. Subgroup analysis and sensitivity analysis were performed during the pooled analysis.ResultsEight studies including 2571 patients were included. The pooled results indicated that patients in the high NPS group exhibited significantly worse overall survival (HR= 2.08 95%CI: 1.74-2.48; P<0.01; I2 = 0%) and disease-free survival (HR=2.03; 95%CI: 1.49-2.77; P<0.01; I2 = 30%). Notably, the prognostic significance of NPS on both overall survival and disease-free survival was consistent across different geographical regions, tumor stages, and primary treatments examined in this study. Furthermore, sensitivity analyses confirmed the robustness of these combined results.ConclusionThe pretreatment NPS could serve as a valuable biomarker for predicting long-term oncological outcomes in patients diagnosed with colorectal cancer.